The Place of Women in the Armed Forces: Legislation and State Compliance with Gender Equality Policies - Serhii M. Perepolkin; Valentyna O. Boniak; Vitalii A. Zavhorodnii; Tetiana L. Syroid; Liudmyla A. Filianina (Feminist Encounters: A Journal of Critical Studies in Culture and Politics, 2024)
The purpose of this comparative study is to analyse the challenges and problems faced by women during military service based on the state of gender equality in different countries. The study analysed international law and international judicial practise, which are the driving forces behind making adjustments and changes to the legislation of different countries. The main research method was to compare the existing doctrinal approaches to the study of gender inequality in the armed forces of different countries, to display quantitative indicators of women’s military service in those countries, as well as to analyse and compare the nature of the challenges faced by women during their military service. The study also conducted a thorough analysis of the works of scholars in this area, which confirmed the existence of this problem of gender inequality in the armed forces. It was concluded that the authorised bodies of states should allocate significant resources and efforts to implement measures to ensure the rights of women in the armed forces.